Order Vehicle Washing Online System Design Based On Android System - Sama, Hendi; Zulkarnain; Tjahyadi, Surya; Syahputra, Bayu; Siahaan, Mangapul; Muhamad Dody Firmansyah; Hendi Che; Deli (Program Sarjana Sistem Informasi, Universitas Internasional Batam, 2024)
This study aims to design an android-based online vehicle washing order application on mobile that aims to increase ease in placing orders. The application is designed using the sublime code editor using the react native framework. The backend part of this application is designed using the basic PHP language and uses the laravel framework to speed up and simplify development. The medium used to connect between the application and the system is using a JSON-based web service. This research and design produce an android-based mobile system. The results of this design shorten the user's time in placing orders and produce a user satisfaction level of 77.5%.